The predictive value of Gen-Probe's amplified Mycobacterium tuberculosis direct test compared with culturing in paraffin-embedded lymph node tissue exhibiting granulomatous inflammation and negative acid fast stain - Wasim F. Raslan; Ali Rabaan; Jaffar A. Al-Tawfiq (Elsevier, 2014)
Summary: Background and objectives: The diagnosis of granulomatous inflammation with possible tuberculosis (TB) infection in histopathology is often difficult. There is a need for a rapid and reliable diagnostic test. Thus, we evaluated the performance of the Mycobacterium tuberculosis direct (MTD) test in specimens with granulomatous lymphadenitis and negative acid fast stains. Methods: The M. tuberculosis direct (MTD) test by Gen-Probe was performed on 45 formalin-fixed paraffin-embedded tissue samples including 34 lymph nodes. We measured the predictive values of the MTD test in specimens with granulomatous lymphadenitis and negative acid fast stains. Results: The overall test sensitivity was 73.9%, and specificity was 95.4%. The MTD test sensitivity and specificity for lymph node tissue were 72.7% and 91.67%, respectively. In the presence of granulomatous inflammation, the MTD test sensitivity and specificity were higher than those for all tissue samples, at 75% and 100%, respectively. Conclusion: Based on this study, the MTD test should be used as a supportive test in addition to conventional histochemical or immunological staining methods when evaluating lymph node tissue with a granulomatous inflammation to deliver stronger evidence to support clinical decisions at a much earlier time than a culture would allow. Keywords: Tuberculosis, Molecular testing, Granuloma, Mycobacterium tuberculosis direct (MTD) test, Gen-Probe